1996
DOI: 10.1084/jem.183.4.1789
|View full text |Cite
|
Sign up to set email alerts
|

A subclass of dendritic cells kills CD4 T cells via Fas/Fas-ligand-induced apoptosis.

Abstract: SummaryDendritic cells (DC), the most efficient antigen-presenting cells, are well equipped for activation of naive CD4 + T cells by their expression of high levels of major histocompatibility complex and costimulator molecules. We now demonstrate that some DC are equally well equipped for killing these same T cells. Murine splenic DC consist of both conventional CDSot-DC and a major population of CD8cx + DC. Whereas CDS-DC induce a vigorous proliferative response in CD4 T cells, CD8 + DC induce a lesser respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
386
3
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 601 publications
(409 citation statements)
references
References 25 publications
19
386
3
1
Order By: Relevance
“…Earlier studies from this laboratory documented several ways in which CD8 + DC, freshly isolated from non-infected steady state mice, limited the proliferative response of interacting T cells, compared to CD8 -DC [28,29]. We now confirm that freshly isolated CD8 + DC induce poor CD4 T cell proliferation compared to CD8 -DC in a variety of antigen presentation assays, across a broad range of antigen concentrations and DC doses.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Earlier studies from this laboratory documented several ways in which CD8 + DC, freshly isolated from non-infected steady state mice, limited the proliferative response of interacting T cells, compared to CD8 -DC [28,29]. We now confirm that freshly isolated CD8 + DC induce poor CD4 T cell proliferation compared to CD8 -DC in a variety of antigen presentation assays, across a broad range of antigen concentrations and DC doses.…”
Section: Introductionsupporting
confidence: 72%
“…We compared normal DC with DC from FasL-mutant C3H/HeJ.gld mice [35]. A selective staining of CD8 + DC was obtained as in the previous study [28], but the same strong staining was obtained with CD8 + DC from the FasL-mutant C3H/ HeJ.gld mice, suggesting an unspecific staining (data not shown). It was concluded that freshly isolated splenic CD8 + DC did not express conventional FasL, despite their selective binding of a Fas-Fc construct.…”
Section: The Role Of Fas-fasl Interaction In the Reduced Stimulatory supporting
confidence: 53%
See 3 more Smart Citations